“Inong” Aceh: Partisipasi Perempuan dalam Pembangunan dan Ruang Publik di Aceh - Nova, Mirza Adia; Syam, Futri; Witria, Syalva (AL-UKHWAH - JURNAL PENGEMBANGAN MASYARAKAT ISLAM, 2023)
This article analyzed about women's participation in development and the public sphere is important in inclusive and sustainable community development. In Aceh, a province with a strong cultural and religious background, issues of gender and women's leadership are of particular interest. Strong cultural norms and social demands often limit women's access to public space and decision-making. This research aims to understand women's contributions to development and the public sphere and the challenges faced, focusing on gender issues and typologies of women's leadership. This study used qualitative research methods by conducting in-depth interviews, participatory observation, and document analysis to collect data. The results show that women's participation in development and the public sphere in Aceh still faces significant challenges. The results show that women's participation in development and the public sphere in Aceh has important implications for achieving inclusive and sustainable development. The research also revealed several typologies of emerging women's leadership, such as community, social, and political leadership. These have played an important role in positive change in various areas, including education, health, economic empowerment, and local decision-making. This women's leadership is driving more equitable and inclusive social change.